1998
DOI: 10.1002/ana.410440621
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating antiganglioside antibodies in primary and secondary progressive multiple sclerosis

Abstract: Plasma samples from 70 patients with multiple sclerosis (MS), 41 patients with other neurological diseases (OND), and 38 healthy subjects were examined for anti-bodies against gangliosides GM1, GM3, GDla, GD1b, and GD3 using enzyme-linked immunosorbent assays. The percentages of subjects with increased anti-GM3 responses were significantly higher in the primary progressive MS (56.3%) and secondary progressive MS (42.9%) groups than in the relapsing-remitting MS (2.9%), healthy subject (2.6%), and OND (14.6%) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 21 publications
3
95
0
Order By: Relevance
“…These antigens are bound via their acyl chains in the deep hydrophobic groove of the MHC-like CD1 molecule so that their hydrophilic components are positioned for highly specific interactions with T cell antigen receptors. 28 The increased T cell reactivity to GM3 fits with our previously reported finding of increased circulating anti-GM3 antibodies in primary progressive MS 12 ; we did not measure anti-GQ1b antibodies in that study. The present study also suggests that patients with relapsing-remitting or secondary progressive MS have increased T cell reactivity to GM3, whereas our previous study found anti-GM3 antibodies to be normal in relapsing-remitting MS and increased in secondary progressive MS, although less so than in primary progressive disease.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These antigens are bound via their acyl chains in the deep hydrophobic groove of the MHC-like CD1 molecule so that their hydrophilic components are positioned for highly specific interactions with T cell antigen receptors. 28 The increased T cell reactivity to GM3 fits with our previously reported finding of increased circulating anti-GM3 antibodies in primary progressive MS 12 ; we did not measure anti-GQ1b antibodies in that study. The present study also suggests that patients with relapsing-remitting or secondary progressive MS have increased T cell reactivity to GM3, whereas our previous study found anti-GM3 antibodies to be normal in relapsing-remitting MS and increased in secondary progressive MS, although less so than in primary progressive disease.…”
Section: Discussionsupporting
confidence: 84%
“…Convincing evidence that immune responses against gangliosides may indeed cause axonal degeneration has been provided by the induction of experimental sensory ataxic neuropathy in rabbits by immunization with GD1b, a ganglioside found in dorsal root ganglion neurons and dorsal root axons. 3 Several studies have found increased antiganglioside antibody levels in the sera and/or cerebrospinal fluid (CSF) of patients with MS. 4,5,6,7,8,9,10,11,12,13 Acarin et al 11 and Sadatipour et al 12 compared the levels among the subtypes of MS and showed increased antiganglioside antibody levels in patients with primary progressive MS. Several studies have also demonstrated increased peripheral blood T lymphocyte responses to mixed ganglioside preparations in patients with MS. 14,15,16,17,18 However, there have been no studies comparing T cell reactivity to individual gangliosides among the relapsing-remitting, secondary progressive and primary progressive forms of MS. The present study was performed to determine the T cell responses to individual gangliosides in the different forms of MS. We found increased peripheral blood T cell proliferative responses to GM3 and GQ1b gangliosides in patients with primary progressive MS.…”
Section: Introductionmentioning
confidence: 99%
“…33 These findings raise the possibility that disease progression is related to antibodymediated CNS damage. Patients with primary progressive MS have increased serum antiganglioside antibody levels compared to those with relapsing-remitting MS and controls; 34,35 the levels in secondary progressive MS tend to be intermediate between those in primary progressive MS and relapsing-remitting MS. 35 Furthermore, antibodies to light neurofilament subunit, an axonal cytoskeletal protein, are increased in the CSF in primary and secondary progressive MS compared to relapsing-remitting MS. 36 Antibodies to CNS antigens could contribute to progression by causing demyelination or axonal damage or by inhibiting remyelination. Further definition of these antibodies might lead to advances in the diagnosis and prognosis of primary progressive MS.…”
Section: Antibodymentioning
confidence: 99%
“…25 The lack of remyelination raises the possibility that immune attack might prevent remyelination in primary progressive MS and that demyelination without remyelination could be an important mechanism for disease progression. One possible immune mechanism for inhibiting remyelination is the action of antiGM3 antibodies which are elevated in the sera of patients with primary progressive MS; 35 these antibodies might interfere with the important role that GM3 ganglioside has in the differentiation of oligodendrocyte progenitors toward myelin production. 45 …”
Section: Remyelinationmentioning
confidence: 99%
“…Mechanisms of transition and differences between the various forms of MS are not well understood, due in part to the bias towards research on RR disease based on the availability of animal models (Thompson et al, 1997). PP-MS is clinically, epidemiologically, pathologically, and immunologically different from the other forms of MS (Pender et al, 2003;Sadatipour et al, 1998), which begs the question whether PP-MS and RR-MS are two distinct diseases (Larsen et al, 1985;McDonald, 1994;Olerup et al, 1989).…”
Section: Introductionmentioning
confidence: 99%